MANAGERIAL VERSUS PROFESSIONAL CONTROL : THE CASE OF PERFORMANCE APPRAISAL IN UK UNIVERSITIES /: THE CASE OF PERFORMANCE APPRAISAL IN UK UNIVERSITIES. (December 2007) - McCourt, Willy; Moores, Josie
No abstract available